PENGARUH METODE LATIHAN PUSH-UP DAN LATIHAN CLAPPING PUSH-UP TERHADAP DAYA LEDAK OTOT LENGAN STUDY KASUS PADA ATLET PENCAK SILAT TUAH PANDEKA RAJO - Rezky Hidayat; Pudia M Indika (JURNAL STAMINA, 2018)
The problem in this study is the low explosive power of the arm of the martial arts athlete in the martial arts. The purpose of this study was to determine the differences in the effect of push-up exercises and push-up clapping exercises on the explosive power of the rajo martial arts athletes.This type of research is experimental. This research was carried out at the Rajo martial arts school. The population in this study were all pencak silat athletes in the Rajo-themed college with a total of 15 sons, the sampling used a purposive sampling technique. Thus the sample in this study was a martial arts athlete with a number of ten sons. The technique of collecting data by testing two hand medicine ball put. The data was analyzed by a statistical calculation of the average count (t-test) at a significant level α = 0.05. The results of the study were as follows: 1) Push-up exercises were effective in increasing the explosive power of the rajo martial arts athletes, 2) Clamping push-up exercises were effective in increasing the explosive power of the arm of the martial arts athlete, rajo, 3) Exercise Clapping push-ups are more effective than push-up exercises for the explosive power of the arm muscles of a martial arts athlete tuah pandeka rajo. Abstrak Masalah dalam penelitian ini adalah masih rendahnya daya ledak otot lengan atlet pencak silat tuah pandeka rajo. Tujuan penelitian ini adalah untuk mengetahui perbedaan pengaruh latihan push-up dan latihan clapping push-up terhadap daya ledak otot lengan atlet pencak silat tuah pandeka rajo. Jenis penelitian ini adalah exsperimen. Penelitian ini dilaksanakan di perguruan pencak silat tuah pandeka rajo. Populasi dalam penelitian ini adalah seluruh atlet pencak silat di perguruan tuah pandeka rajo yang berjumlah 15 orang putra, penarikan sampel menggunakan teknik purposive sampling. Dengan demikian sampel dalam penelitian ini adalah atlet pencak silat tuah pandeka rajo yang berjumlah 10 orang putra. Teknik pengambilan data dengan tes two hand medicine ball put. Data di analisis dengan uji statistik beda rerata hitung (t-test) pada taraf signifikan α=0,05.Hasil penelitian diperoleh sebagai berikut: 1) Latihan push-up efektif dalam peningkatan daya ledak otot lengan atlet pencak silat tuah pandeka rajo, 2) Latihan clapping push-up efektif dalam peningkatan daya ledak otot lengan atlet pencak silat tuah pandeka rajo, 3) Latihan clapping push-up lebih efektif dari pada latihan push-up terhadap daya ledak otot lengan atlet pencak silat tuah pandeka rajo.